Reframing Destination Brand Experience: A Systematic Review Of Its Influence On Tourist Satisfaction and Loyalty In Cultural Tourism - Faliti, Adam Faisal; Atmoko, Andreo Wahyudi (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
This study presents a systematic literature review (SLR) of 35 global and Indonesia-based scholarly articles to investigate how Destination Brand Experience (DBE) influences tourist satisfaction and loyalty, particularly within the domain of cultural tourism. The review adopts a hybrid SLR and interpretive synthesis approach to evaluate the impact of four DBE dimensions—sensory, affective, behavioral, and intellectual—on visitor experience outcomes. Drawing on the Expectancy-Disconfirmation Theory, the review highlights satisfaction as a key mediating factor between DBE and tourists’ revisit and recommendation intentions. Findings show that while DBE is widely recognized as a multidimensional construct in tourism literature, empirical research remains concentrated in Western, festival, or nature-based settings. The case of Taman Mini Indonesia Indah (TMII) is examined to contextualize these findings in a revitalized cultural theme park in the Global South. This review proposes a conceptual framework for future empirical testing and suggests strategic directions for enhancing experience-based destination branding in culturally diverse and emerging tourism economies.